AN ANALYSIS OF METAPHOR USED ON SELECTED SONG FROM ALBUM OVEREXPOSED BY MAROON 5 - Ahmad Adi Syukron; Dias Andris Susanto; Fitri Yulianti (Universitas 17 Agustus 1945 Semarang, 2025)
This study explores the use of metaphors in five selected songs from Maroon 5’s Overexposed album (2012) by applying Lakoff and Johnson’s (1980) Conceptual Metaphor Theory. Using a qualitative descriptive approach, the research identified three types of metaphors such as: structural metaphor, ontological metaphor, and orientational metaphor. The findings reveal a total of 32 metaphorical expressions across the five selected songs. Ontological metaphors emerged as the most dominant type (47%), followed by structural metaphors (37%) and orientational metaphors (16%). The findings show that metaphors in the lyrics are not only artistic devices but also cognitive tools that help express abstract concepts such as love, pain, and emotional struggle in relatable ways. This study contributes to stylistics by demonstrating the richness of figurative language in popular music and highlights the potential of song lyrics as engaging resources for teaching and learning English, particularly in understanding figurative language and discourse analysis.